2019
DOI: 10.1177/1362361318818327
|View full text |Cite
|
Sign up to set email alerts
|

Anglo-Latino differences in parental concerns and service inequities for children at risk of autism spectrum disorder

Abstract: In an evaluation of Anglo and Latina mothers and their children at risk of autism, this study compared mother-reported child behavioral concerns to staff-observed symptoms of autism. Within Latina mothers, the impact of primary language (English/Spanish), mothers’ education, and child age on ratings of developmental concerns was examined. Participants were 218 mothers (Anglo = 85; Latina = 133) of children referred to a no-cost autism screening clinic. Mothers reported on behavioral concerns, autism symptomolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Additionally, socio-demographic and culturally determined factors, such as the knowledge the general population possesses about developmental milestones ( Ratto et al, 2016 ), caregivers’ ability to recognize early emerging symptoms ( Mandell and Novak, 2005 ), and misconceptions about signs, symptoms, and etiology ( Rahbar et al, 2011 ) can play a role in trajectories toward identification. For instance, a study performed in the United States with mothers from a Latin-American origin reported significantly fewer developmental concerns and fewer ASD symptoms in children diagnosed with ASD in this group, compared to Anglo-American mothers, possibly due to lower ASD awareness, parental practices, or the presence of perceptions concealing the recognition of symptoms ( Blacher et al, 2019 ). Another United States study with families of Mexican heritage reported that parents expect children to show respect for their elders by not speaking to them unless they are spoken to, suggesting that in this context, a lower level of communication might not be acknowledged as concerning ( Bridges et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, socio-demographic and culturally determined factors, such as the knowledge the general population possesses about developmental milestones ( Ratto et al, 2016 ), caregivers’ ability to recognize early emerging symptoms ( Mandell and Novak, 2005 ), and misconceptions about signs, symptoms, and etiology ( Rahbar et al, 2011 ) can play a role in trajectories toward identification. For instance, a study performed in the United States with mothers from a Latin-American origin reported significantly fewer developmental concerns and fewer ASD symptoms in children diagnosed with ASD in this group, compared to Anglo-American mothers, possibly due to lower ASD awareness, parental practices, or the presence of perceptions concealing the recognition of symptoms ( Blacher et al, 2019 ). Another United States study with families of Mexican heritage reported that parents expect children to show respect for their elders by not speaking to them unless they are spoken to, suggesting that in this context, a lower level of communication might not be acknowledged as concerning ( Bridges et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also note that among studies included in the current review, most participants were Caucasian. Unfortunately, the lack of ethnic diversity in participant populations may be due to documented disparities in the age of initial screening/diagnosis of ASD among traditionally minoritized groups [ 2 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, going forward, telehealth ASD assessment may become an “equalizer,” bringing the possibility of diagnosis and early intervention to all families, regardless of socioeconomic, racial, or ethnic status. For too long, there have been disparities in access to early autism identification and in families' understanding of autism (Blacher et al, 2019 ). With such new procedures, conducted in Spanish as well as English, timely access to those living in rural and desert areas will be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the lack of service providers in rural areas, who conduct early screening and diagnosis, places entire communities at risk of not having children with ASD identified as needing services (Elder et al, 2016 ; Janvier et al, 2016 ). In addition, there are pervasive ethnic disparities evident in autism‐related services in many areas of the country (Blacher et al, 2019 ; Zuckerman et al, 2014 , 2017 ). On average, children from Latinx families are diagnosed later (and/or less frequently) than children from non‐Latinx families (Baio et al, 2018 ; Maenner et al, 2020 ; Mandell et al, 2002 ; Zuckerman et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%